Strategy To Improve Employee Performance - Wahyudi Wahyudi; Dedeh Kurniasih; Didit Haryadi; Fitria Haquei (Institute of Computer Science (IOCS), 2022)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become the locomotor in making a real contribution to the organization's success on an ongoing basis. Of course, only employees with optimal performance achieve this success. However, to maximize employee performance, there must be a strategy to improve it. This study aims to determine how this strategy improves employee performance. The PLS-SEM approach was used in this study. The results of this study show that the roles of coaching, intrinsic motivation, and employee creativity can be driving forces in the strategy to optimally increase employee performance, either directly or indirectly